Personal Word Lists: Strategy to Build Learners' Vocabulary - Fudhla, Nora (Edu-Ling: Journal of English Education and Linguistics, 2018)
Vocabulary learning is one of the major challenges second/foreign language learners find during the process of learning a language. One way to alley the burden is to assist students in becoming independent learners during the process of vocabulary learning. It could be achieved through instructing learners to apply vocabulary learning strategies as efficient as possible. The main pursuit of the present article is to suggest a vocabulary learning strategy for training EFL learners in acquiring the target words. The vocabulary learning strategy meant here named Personal Word Lists. This strategy helps the learners to enrich their vocabulary acquisition considering the multiple forms of strategies, such as cognitive, memory, metacognitive, activation and affective strategies. The multiple forms of those strategies are implied through note-taking, imagery mediation, background knowledge relations, semantic mapping/elaboration, senses, rehearsal and encoding strategies. In doing so, the basic concepts of vocabulary learning strategies and rationale or sample for strategy application are presented. It is assumed that this strategy may lead the learners to reach meaningful representation and enhance their vocabulary acquisition.